A Method of calculating the compressive strength of Z-stiffened panels that develop local instability - Gallaher, George L. (National Advisory Committee for Aeronautics, 1947)
A method, based on the elastic theory for plate buckling and test results for 24S-T aluminum-alloy Z-stiffened panels, is shown for calculating the compressive strength of Z-stiffened panels that develop local instability. This method can be used to calculate the critical compressive stress above, as well as within, the elastic range. For stresses above three-fourths the compressive yield stress the method can be used for the approximate determination of the average compressive stress at maximum load.
"November 1947."
NACA TN No. 1482.
Keywords: Plates (Engineering); Strains and stresses.; Buckling (Mechanics); Mathematical analysis.; elektronické knihy; electronic books